(untitled) (Italian Review of Legal History, 2015)
The rule set in the Italian civil code of 1865 forbidding investigation about paternity out of wedlock was deeply innovative in comparison with judiciary practices in the Middle and Modern ages, as well as in comparison with early-XIX-century, pre-Unity legislation on the matter. The rule raised therefore a wide debate in doctrine, with a strongly engaged field of civil lawyers demanding a reform of the code; however, it was also the occasion of a florid casuistry, with special regard the solution of problems in the application of transitory rules. The situation in the territories formerly belonging to the Lombardo-Veneto was particularly complex, given thay they had been subjected to the quite different rules provided by the Austrian ABGB.